Factors associated with insufficient cervical ripening in a controlled-release dinoprostone vaginal delivery system: A single perinatal center retrospective study - Ayako Takizawa; Youhei Tsunoda; Takashi Matsushima; Shunji Suzuki (Elsevier, 2024)
Objective: In this study, we aimed to evaluate the factors associated with insufficient cervical ripening in a controlled-release dinoprostone vaginal delivery system (Propess). Materials and methods: This retrospective cohort study included 103 pregnant women who used Propess for labor induction. The outcomes were the factors associated with insufficient cervical ripening, defined as a Bishop score ≤6 on the morning after Propess administration. Results: Forty-nine participants had insufficient cervical ripening, and 54 had sufficient cervical ripening. Univariate analysis of these two groups showed that maternal age ≥35 years, early-term delivery (gestational age between 37 and 38 weeks), and Bishop scores at insertion ≤1 were significantly higher in the insufficient cervical ripening group. Multivariate logistic analysis showed that maternal age ≥35 years (adjusted odds ratio: 3.08, 95% confidence interval: 1.29-7.36, p = 0.011) and early-term delivery (adjusted odds ratio: 3.17, 95% confidence interval: 1.23-8.20, p = 0.017) were independent factors associated with poor Propess efficacy. Parity, pre-pregnancy body mass index, body mass index at delivery, and indications for labor induction were not associated with insufficient cervical ripening. Conclusions: In our study, older maternal age and early-term delivery were independent predictors of insufficient cervical ripening with Propess. More effective delivery management can be achieved by considering induction protocols tailored to individual maternal factors for patients with factors associated with poor Propess efficacy.